Application Information Technology For Posyandu Cadres: SI-MASTING For Early Detection of Stunting - Rina Sri Widayati; Nur Amalina; Galih Pramuja Inngam Fanani; Suratman Suratman; Aulia Uswatun Khasanah; Riyani Wulandari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Stunting remains a major public health issue in Indonesia, with a prevalence of 21.6% in 2022 (SSGI). Early detection at Posyandu is often constrained by manual recording, which is time-consuming, error-prone, and difficult to integrate with health systems. This study aimed to implement SI-MASTING (Stunting Early Detection Information System) to improve the effectiveness and accuracy of child growth monitoring. The study was conducted at Posyandu Sanggrahan, Sukoharjo, involving 95 cadres through Focus Group Discussions (FGDs) and User Acceptance Testing (UAT), along with trials on 11 toddlers. Results showed that SI-MASTING reduced the average recording time from 7.1 minutes to 2.4 minutes per child (66.2% efficiency) and decreased the error rate from 15.4% to 2.1% (86.3% accuracy improvement). Detection of children at risk of stunting increased from 48% to 92% (44% improvement). Cadre satisfaction was high, with an average score of 4.52 out of 5; ease of use received the highest rating of 4.67, followed by application speed at 4.58. In case testing, 45% of toddlers were identified as stunted, with the highest prevalence of 50% in the 12–18 month age group. In conclusion, SI-MASTING effectively accelerates early stunting detection, enhances data accuracy, and empowers cadres in nutritional interventions. The system has strong potential for integration with e-Puskesmas and replication in other regions as part of the national strategy to accelerate stunting reduction.